2017
DOI: 10.1099/jgv.0.000801
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance between innate antiviral and pro-inflammatory immune responses may contribute to different outcomes involving low- and highly pathogenic avian influenza H5N3 infections in chickens

Abstract: In order to gain further insight into the early virus-host interactions associated with highly pathogenic avian influenza virus infections in chickens, genome-wide expression profiling of chicken lung and brain was carried out at 24 and 72 h post-inoculation (h p.i.). For this purpose two recombinant H5N3 viruses were utilized, each possessing a polybasic HA0 cleavage site but differing in pathogenicity. The original rH5N3 P0 virus, which has a low-pathogenic phenotype, was passaged six times through chickens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In the current study, MX1 expression was upregulated with a log 2 fold change of 3.69 in the DBE group, which is similar to the result for RSAD2. According to Pasick et al [40], the MX1 gene may be involved in the inhibition of influenza A virus replication by preventing primary viral mRNA synthesis in laying hens. We speculate that the up-regulation of MX1 expression in the liver may protect laying hens from viral diseases that are responsible for decreasing intensity of brown eggshell color.…”
Section: Up-regulated Genes In Laying Hens With Dbementioning
confidence: 99%
“…In the current study, MX1 expression was upregulated with a log 2 fold change of 3.69 in the DBE group, which is similar to the result for RSAD2. According to Pasick et al [40], the MX1 gene may be involved in the inhibition of influenza A virus replication by preventing primary viral mRNA synthesis in laying hens. We speculate that the up-regulation of MX1 expression in the liver may protect laying hens from viral diseases that are responsible for decreasing intensity of brown eggshell color.…”
Section: Up-regulated Genes In Laying Hens With Dbementioning
confidence: 99%
“…The RNA used for qRT-PCR was prepared in the same way as the total RNA extraction and DNase I treatment described above. Five genes were selected based on their functions in the immune response as reported in other chicken studies and significance within the RNA-seq results ( Pasick et al, 2017 , Smith et al, 2015 , Rychlik et al, 2014 ). Primer pairs were designed using Primer3 ( Rozen and Skaletsky, 2000 ) and their primer sequences are listed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, the creation of a transgenic chicken expressing the duck RIG-I has been under patent since 2010 (US20110247091A1). However, it is important to recognise that even in the absence of a RIG-I homologue, chickens still mount a pronounced antiviral response to HPAI virus infections in vivo [ 25 , 26 ]. Indeed, it has been suggested that melanoma differentiation factor (MDA5), a RIG-I like sensor, is able to compensate for the absence of RIG-I in chickens [ 27 ].…”
Section: Rig-i: a Transgene Of Interest?mentioning
confidence: 99%